Investigating EFL Teachers’ Barriers of Using Internet Application at University Level - Dewi, Dian Novita; Irmawati, Dini Kurnia; Asri, Tri Mega (Universitas Muhammadiyah Sidoarjo, 2020)
This study examines perceived barriers of using internet application in higher education level. Quantitative data were collected by using questionnaires. A total of 16 participants assigned to teach English were randomly selected from 3 faculties using both simple random and purposive sampling procedures. Data were analyzed both descriptively and statistically and were presented in tables and percentages. Microsoft excel was used in the descriptive statistics The study found several barriers of using internet application for teaching and learning which include: lack of personal’s ICT competency, lack of consistent technical support, lack of training on how to use internet application for teaching and learning, and poor internet connectivity. This study recommends to the management of the institution to facilitate and support the teachers actively with many training activities to improve the academic performance of the teachers so that can fulfill the millennial students’ learning needs. HIGHLIGHTS: English teachers have strong intention for the integration of ICT into classroom context, but they encountered many barriers to implement it. The major barriers faced in this study were lack of facilities or infrastructure, training, and time constraint. The presence of ICT competency increases technology integration in learning and teaching process.